ANALISIS DAYA SAING DAN KEBIJAKAN PEMERINTAH PADA USAHATANI CABE MERAH (KASUS KECAMATAN CIWIDEY KABUPATEN BANDUNG DAN KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT) - Netti Tinaprilla (Jurnal Agribisnis dan Ekonomi Pertanian, 2008)
This paper aims to analyze (1) profitability of chili farming privately and socially; (2) competitiveness of chili through competitive and comparative advantages; (3) impacts of government policy on chili farming; (4) impacts of the government policy change on the competitiveness of chili. This research was conducted in Ciwidey sub-district, Bandung district and Lembang sub-district, Bandung Barat district. Both primary and secondary data were used in this research whereas the samples were chosen by snowball sampling method. Policy Analysis Matrix (PAM) was employed in this paper. The survey was conducted from December 2007 to February 2008. The results showed that chili farming in both sub-districts was profitable privately and socially. Chili farming in Lembang was more profitable than in Ciwidey. Both sub-districts have competitive and comparative advantages where the competitive and comparative advantages in Ciwidey were higher. Impacts of output policy have caused the chili farming in both sub-districts received actual output price lower that its social price. Subsidy of tradable and non-tradable inputs caused farmers received cheaper input price. Government policy on input-output has benefited chili farming in Lembang. Increase of production cost, decrease of output price and decrease of production partially or as a whole have caused smaller profitability and higher PCR and DRC that are nearly to one. However, these changes would not change the profit to be the loss or competitive and comparative advantages to be not competitive.